SARS-COV-2 Infection and Kawasaki Disease: Case Report of a Hitherto Unrecognized Association - Cazzaniga, Marco; Baselli, Lucia Augusta; Cimaz, Rolando; Guez, Sophie Suzanne; Pinzani, Raffaella; Dellepiane, Rosa Maria (Frontiers in Pediatrics, 2020)
Coronavirus-associated disease (COVID-19) was firstly reported at the end of 2019. Generally, COVID-19 seems to be a less severe disease in children than in adults. According to the current literature, children account approximately for 2% of diagnosed COVID-19 cases. Northern Italy is one of the geographical areas mainly affected by the ongoing COVID-19 pandemic. We describe a pediatric patient diagnosed and treated for atypical/incomplete Kawasaki Disease (KD) complicated with paralytic ileus, who also resulted positive for SARS-COV-2.